Philosophical writings - Strawson, P. F.; Strawson, Galen; Montague, Michelle (Oxford : Oxford University Press, 2011)
This volume presents 22 uncollected philosophical essays by Sir Peter Strawson, one of the leading philosophers of the second half of the 20th century. The essays are drawn from seven decades of work, and span all the central areas of philosophy along with metaphilosophical reflections and intellectual autobiography.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Strawson, P. F